2007
DOI: 10.1210/me.2006-0005
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-Induced Neural Differentiation via Angiotensin II Type 2 (AT2) Receptor-MMS2 Cascade Involving Interaction between AT2Receptor-Interacting Protein and Src Homology 2 Domain-Containing Protein-Tyrosine Phosphatase 1

Abstract: Angiotensin II (Ang II) type 2 (AT2) receptors are abundantly expressed not only in the fetal brain where they probably contribute to brain development, but also in pathological conditions to protect the brain against stroke; however, the detailed mechanisms are unclear. Here, we demonstrated that AT2 receptor signaling induced neural differentiation via an increase in MMS2, one of the ubiquitin-conjugating enzyme variants. The AT2 receptor, MMS2, Src homology 2 domain-containing protein-tyrosine phosphatase 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 47 publications
4
91
0
Order By: Relevance
“…In this study, we observed that direct stimulation of the AT 2 receptor enhanced neurite elongation in hippocampal neurons. Moreover, AT 2 receptor stimulation directly enhances synaptic plasticity as reported previously (Li et al, 2005(Li et al, , 2007Reinecke et al, 2003). Therefore, the increase in f-EPSP observed in the hippocampus of mice treated with C21 could be caused by neurite elongation, synaptic augmentation, and increased electrotonic coupling.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, we observed that direct stimulation of the AT 2 receptor enhanced neurite elongation in hippocampal neurons. Moreover, AT 2 receptor stimulation directly enhances synaptic plasticity as reported previously (Li et al, 2005(Li et al, , 2007Reinecke et al, 2003). Therefore, the increase in f-EPSP observed in the hippocampus of mice treated with C21 could be caused by neurite elongation, synaptic augmentation, and increased electrotonic coupling.…”
Section: Discussionsupporting
confidence: 59%
“…The contradictory effect of Ang II on cellular proliferation versus apoptosis has been hypothesized to be determined by cell-typespecific expression of the receptors as well as differences in downstream signaling. The activation of SHP-1 and SHP-2 protein phosphatases is considered one of the most crucial downstream effects of Ang II, and is believed to mediate negative crosstalk between AT2 with AT1 and possibly with other growth-factor receptors (Alvarez et al, 2008;Bedecs et al, 1997;Cui et al, 2001;Li et al, 2007;Marrero et al, 1998;Matsubara et al, 2001;Wu et al, 2004). In some cells, it has been demonstrated that Ang-II treatment activates opposing signals through simultaneous AT1 and AT2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ATIP seems to act as a potential novel early component of the growth and/or differentiation-regulating signalling cascade mediated by the AT 2 receptor. 15 …”
Section: Evading Growth Suppressorsmentioning
confidence: 99%